If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3k + 3k = -2k + -6 Combine like terms: -3k + 3k = 0 0 = -2k + -6 Reorder the terms: 0 = -6 + -2k Solving 0 = -6 + -2k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '2k' to each side of the equation. 0 + 2k = -6 + -2k + 2k Remove the zero: 2k = -6 + -2k + 2k Combine like terms: -2k + 2k = 0 2k = -6 + 0 2k = -6 Divide each side by '2'. k = -3 Simplifying k = -3
| -5x+12=-7x+2 | | 18+N=23 | | -1+9(x-5)=13x+6-4x | | -7ts+2t^2-4s=0 | | 19=-3x-8 | | 2-3(2x-6)=4((2x)-(1/4)) | | -12-9=n | | 7x7/6 | | 7k-4-5=3+4K | | 2+10=7t-14 | | (2n-8)/3=5/4 | | -19-(-3)-17+(-22)= | | x/7-7-8 | | 2-3(2x-6)=4(2x-(1/4) | | 6f+27=18f+39 | | 10+4m=-2 | | 3=65(2x+5) | | 2b+4=18-ab | | 9/x=6/2 | | 3 = 65(2x+5) | | 6x+15=-3(ax+b) | | 2x-4÷3x-6=2/3 | | .3x+7=4x+9 | | 0.10+(0.15)(20)=(0.12)(x+20) | | 10+6y=28 | | (2x+2y)=(2x+y) | | -6(-4x+3)=6(-4x-3) | | y^2+.4y-.05=0 | | x-(x-7/5)=3(x-34) | | 2/x-1=4/x^2-1 | | 2x+25=17 | | 5x+5=3x-7+3x |